An approach to enhancing energy performance in residential buildings in hot climate regions (The case of Saudi Arabia) - Alyami, Mana (2022)
Saudi Arabia, like many developing countries, is experiencing rapid urbanisation and infrastructure expansion, especially in the area of residential buildings. As an oil-producing nation with an extremely hot climate, the country is also renowned for high rates of energy consumption and carbon emissions. The construction sector is no exception, accounting for approximately 80% of total national electricity consumption, with residential cooling demand consuming almost 66% of domestic energy use. Although sustainability has now become a major focus for the Saudi government, with sustainable development being a key goal of the country’s economic and social development plan, the Saudi Vision 2030, the lack of energy efficiency in Saudi buildings has yet to be given serious consideration. However, with current demand threatening long-term energy security and forecasts indicating that domestic energy consumption will rise at a rate of 5% to 7% annually, it is crucial to improve the energy and environmental performance of the building stock.